Unravelling the complex interplay of cuproptosis, lncRNAs, and immune infiltration in Alzheimer’s disease: a step towards novel therapeutic targets - Yi Zeng; Siqi Qian; Yuan Cao; Wenbiao Xiao (Annals of Human Biology)
Background Cuproptosis, a type of cell death involving copper ion accumulation and oxidative stress, has been implicated in the development of Alzheimer’s disease (AD).Aim This study aimed to explore the potential mechanisms and roles of cuproptosis-related genes (CRGs), long non-coding RNAs (lncRNAs), and immune cells in the development of cuproptosis in AD.Subjects and methods Gene expression profiles of AD were acquired from the Gene Expression Omnibus (GEO) database, and differential analysis was conducted to identify CRGs. Random Forest (RF) modelling was employed to select the most crucial CRGs, which were subsequently validated in the test set. A nomogram model was created to predict AD risk and categorise AD subtypes based on the identified CRGs. A lncRNA-related ceRNA network was built, and immune cell infiltration analysis was conducted.Results Twelve differentially expressed CRGs were identified in the AD dataset. The RF model pinpointed the five most critical CRGs, which were validated in the test set with an AUC of 0.90. A lncRNA-related ceRNA network was developed, and immune cell infiltration analysis revealed high levels of M1 macrophages and mast cells, along with low levels of memory B cells in AD samples. Correlation analysis unveiled associations between CRGs, lncRNAs, and differentially infiltrating immune cells.Conclusion This research offers insights into the potential mechanisms and roles of CRGs, lncRNAs, and immune cells in the development of cuproptosis in AD. The identified CRGs and lncRNAs may serve as potential therapeutic targets for AD, and the nomogram model may assist in early AD diagnosis and subtyping.